Evaluation of protamine/pDNAlanionic PAMAM dendrimer ternary complexes for hMSCs osteogenic differentiation induction - Moreira, Fátima José Batista (2022)
The control of human Mesenchymal Stem Cells (hMSCs) differentiation towards the os- teoblastic lineage is very important, especially in tissue engineering and regenerative medicine. In this context, Bone Morphogenetic Protein 2 (BMP-2), a known osteogenic differentiation factor, can be applied for hMSCs differentiation using a gene delivery approach. The main goal of the thesis was to develop new non-viral systems for the delivery of the BMP-2 gene into hMSCs based on protamine (PS) and anionic poly(amidoamine) dendrimers (PAMAM-COOH). First, PS/pDNA binary complexes were prepared, where pDNA was efficiently packed, neutralized and protected from serum nucleases. Gene expression levels using these binary complexes and HEK 293T cells were, however, in- significant (EGFP and luciferase reporter genes were used in these studies). So, PS/pDNA/ PAMAM-COOH ternary complexes were then prepared using non-cytotoxic PS/pDNA complexes at a N/P of 7 (N = guanidinium groups in protamine; P = phosphate groups in the pDNA backbone) and several generations of dendrimers (G0.5, G1.5 and G4.5) at C/P ratios of 4, 8 and 12 (C = carboxylate groups in the dendrimer; P = phosphate groups in the pDNA backbone). This was done to see if the combination with an anionic polymer could weaken the electrostatic bonds within the binary complex and increase gene expres- sion. A small improvement in transfection efficiency was, indeed, observed although the values remained very low, far from what was expected. Notwithstanding, one decided to proceed with the best performing ternary complexes and evaluate their behaviour in the transfection of hMSCs with a pDNA encoding BMP-2. Here, it was hypothesized that low transfection levels could still induce the osteogenic differentiation of hMSCs. Compared to the control with dexamethasone (a strong inducer of osteogenesis), the differentiation of hMSCs towards the osteoblastic lineage occurred but to a very low extent, as assessed by classical markers of the process.